A novel orange-red Sm3+-doped CaSiO3 nanostructured phosphor derived from agro food waste materials for white light applications. Issue 19 (1st October 2021) - Krishnam Raju, M.; Prasada Rao, R.; Vijayan, N.; Abdul Azeem, P.
Abstract: Trivalent samarium activated β-Wollastonite (β-CaSiO3 :Sm 3+ ) nanostructured phosphor powders have been synthesized by modified sol-gel method at various concentrations (0.0, 0.2, 0.4, 0.6, 0.8 and 1 mol %) employing rice husk ash (RHA) and eggshell (ES) as the precursors for SiO2 and CaO respectively. The powder x-ray diffraction peaks disclose structure of sintered samples as monoclinic structure with space group P1 21/c1. The average crystallite sizes were determined by Debye scherrer's formula in the range of 26–34 nm. The average particle size was 84.5 nm found from TEM images. The photoluminescence excitation (PLE) spectra recorded high intensity peak at 400 nm was owing to 6 H5/2  →  4 K11/2 transition. The emission (PL) spectra of prepared samples exhibit intense orange–red color emission peak at 602 nm due to 4 G5/2 → 6 H7/2 transition. All the prepared samples emission tuned towards white region of the CIE diagram with the increment of Sm 3+ content. This new nanostructured phosphor material could be a probable candidate for white light display and solid-state lighting (SSL) applications.